2015
DOI: 10.5121/ijmpict.2015.6201
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Knowledge Sharing Using Virtual Platforms – A Validation of Unified Theory of Acceptance and Use of Technology (UTAUT)

Abstract: Knowledge sharing is an important initiative in creating competitive advantage. As an important tool in the successful implementation of Knowledge Management (KM), sharing knowledge is seen to be the most important practice and resource which organization possesses. Various organizations have developed strategies to ensure that KM is successful by embedding knowledge sharing practices in their routine work processes. Nowadays, people have been using virtual platforms and web-based technologies, such as INTRODU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The results did not indicate that age and experience moderate the impacts of effort expectancy on behavioral intention. These findings are consistent with other studies in the literature ( 37 ). An additional explanation for the overall finding is based on the backgrounds of the study respondents, as most had experience in using computers and smartphones and the majority were young adults (40 years old or less).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results did not indicate that age and experience moderate the impacts of effort expectancy on behavioral intention. These findings are consistent with other studies in the literature ( 37 ). An additional explanation for the overall finding is based on the backgrounds of the study respondents, as most had experience in using computers and smartphones and the majority were young adults (40 years old or less).…”
Section: Discussionsupporting
confidence: 94%
“…An additional explanation for the overall finding is based on the backgrounds of the study respondents, as most had experience in using computers and smartphones and the majority were young adults (40 years old or less). Another justification may relate to the widespread use of social media among Saudi people, which helps them to be familiar with such platforms ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers found that social influence has a significant influence on the intention to accept new technologies. Social influence has a positive impact on the usage behaviour of the system in context of knowledge sharing behaviour [47]. Further, social belief has significant impact on consumers' intention to shop online [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…'Knowledge' has been a keyword only in the private sector management literature for many years. But recently, researchers have discovered that knowledge is also a very pressing issue in the literature of public sector development informatics because knowledge can be innovatively managed with the power of ICT [8,9,10]. Based on the work of Polanyi [11,12], Nonaka [13] explicates two basic taxonomies of knowledge in organizations: tacit and explicit.…”
Section: Ict-utilized Knowledge Managementmentioning
confidence: 99%